Modelos experimentais de retalho cutâneo randômico dorsal em ratos: uma revisão sistemática - Espósito, Lara Maria Bataglia (Universidade Federal de São Carlos, 2021)
Introduction: One of the most commonly used techniques in plastic surgery is the use of random skin flaps, which have several benefits, but it’s postoperative period is prone to ischemia. However, even with numerous researches on the subject, it isn’t yet established which would be the most adequate experimental model to study methods of prevention and treatment related to tissue ischemia and, consequently, to necrosis. Objective: To systematically approach and expose the random dorsal skin flap models available in the literature, in order to highlight an experimental model that resembles as much as possible clinical practice and generates significant and non-critical necrosis percentages, in order to better investigate factors and treatments related to necrosis. Methods: The selection of studies related to the topic was carried out in the main databases (PubMed, Cochrane Library, LILACS, Web of Science and Scopus), without a fixed initial period until July 2021. Subsequently, the scientific articles that fit were chosen in the previously established inclusion criteria. Results: In the end, 383 studies were evaluated, and the main information about the amount of pedicle, size of the flap, type of base, use of barrier between the skin flap and its bed, lineage and body mass of the animals were presented. It was observed that there’s no standardization regarding the characteristics of the experimental model of random dorsal skin flap, suggesting a monopedicled model, with a cranial base, without barrier placement and with greater ratios. Conclusion: The results obtained indicate that the most suitable model for investigating factors and treatments related to necrosis consists of a flap measuring 9x3 cm, monopedicled, with a cranial base and without the use of a barrier.
Experimental models of random skin flaps in rats: a systematic review
Keywords: Retalho cutâneo; Necrose; Isquemia; Ratos; Skin flap; Necrosis; Rats; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL